Resolution of Hypercortisolemia Following Medical Intervention for Cushing’s Syndrome and Pulmonary Nocardiosis: A Case Study and Literature Review - Winslow, Timothy Brian; Vates, G Edward; Nead, Michael A.; Shafiq, Ismat (Archives of Clinical and Medical Case Reports, 2024)
Ectopic adrenocorticotropic hormone (ACTH)-dependent Cushing syndrome is rare. The onset is rapid with acute presentation of worsening blood pressure, hypokalemia, hyperglycemia, and weakness leading to infections, clot disorder, fractures, and cardiovascular disease. Prompt recognition and treatment of hypercortisolemia are paramount to decreasing mortality. We report a case of a 66-year-old female presenting to the emergency with acute symptoms of hypercortisolemia. The initial work-up confirmed ectopic ACTH-dependent Cushing syndrome (EACS). Computed tomography(CT) of the chest revealed a 4 cm cavitary mass. A lung biopsy confirmed nocardiosis with no malignancy, prompting antimicrobial and steroidogenesis inhibitors treatment. Medical intervention successfully controlled infection and hypercortisolemia leading to the complete resolution of the lung lesion within 3 months. Although the EACS source was unclear, it was suspected to be in association with pulmonary nocardiosis. Early diagnosis, multidisciplinary care, and vigilant monitoring are crucial to decrease morbidity and mortality in Cushing syndrome.